1988
DOI: 10.1152/jappl.1988.65.3.1191
|View full text |Cite
|
Sign up to set email alerts
|

Changes in fiber composition of soleus muscle during rat hindlimb suspension

Abstract: Chronic reduction of gravitational load in the rear limbs of rats to simulate the influence of near-zero gravity in skeletal muscles has been shown previously to elicit atrophy in the soleus muscle. Use of this model by the present investigation indicates that soleus atrophy was characterized by a decline in the number of fibers in groups that contained the slow isoenzyme of myosin and which were classified as type I from intensity of staining to myofibrillar actomyosin adenosinetriphosphatase (ATPase) and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(40 citation statements)
references
References 0 publications
3
34
0
Order By: Relevance
“…This view is supported by three ndings. First, conversion from a type I ber to type II and type II ber to type I has been reported in several animal models (Romanul et al 1967, Booth 1982, Hauschka et al 1987, Templeton et al 1988, Maxwell et al 1992, Jarvis et al 1996, Brunetti et al 1997, Sutherland et al 1998. Furthermore, Meier et al (1997) found transformation of ber type I to type II in multi dus muscle of young patients with idiopathic scoliosis.…”
Section: Discussionmentioning
confidence: 95%
“…This view is supported by three ndings. First, conversion from a type I ber to type II and type II ber to type I has been reported in several animal models (Romanul et al 1967, Booth 1982, Hauschka et al 1987, Templeton et al 1988, Maxwell et al 1992, Jarvis et al 1996, Brunetti et al 1997, Sutherland et al 1998. Furthermore, Meier et al (1997) found transformation of ber type I to type II in multi dus muscle of young patients with idiopathic scoliosis.…”
Section: Discussionmentioning
confidence: 95%
“…It was reported that the contraction time and half relaxation time of skeletal muscle decreased following hindlimb suspension (HERBERT et al, 1988). These results reflected the increase of fast-type myosin isozyme composition (TEMPLETON et al, 1988). If fiber-type transformation from slow-twitch to fast-twitch fibers were to occur following hindlimb suspension, the decrease of glycolytic enzyme in fast-twitch fiber is a contradictory finding.…”
Section: Discussionmentioning
confidence: 98%
“…TEMPLETON et al (1988) reported that following a 4-week suspension of rat hindlimbs, the percent distribution of type I fiber was reduced and that of type ha fiber was significantly increased. On the other hand, RoY et al (1987) reported that no significant changes in fiber-type distribution were observed in either the superficial region of the gastrocnemius or the tibialis anterior muscles following a 4-week hindlimb suspension in rats.…”
mentioning
confidence: 99%
“…The atrophy of the soleus muscle during hindlimb unloading is due to a decrease in fiber size with no change in fiber number (31). The decrease in cross-sectional area of type II (fast) fibers in the unloaded mouse soleus muscle is …”
Section: Atrophy Of Type I Versus Type Ii Fibers In Control and Unloamentioning
confidence: 98%